International relations and the new phase of imperialism: a dialogue between Robert Cox and Nicos Poulantzas - Berringer, Tatiana (Pontifícia Universidade Católica de São Paulo, 2012)
We present a Poulantzian theory of the state as a counterpoint to the idea of “global governance” defended by Robert Cox. Cox is recognized for having introduced the concepts of Marxist Antonio Gramsci into the theoretical debate on international relations. Poulantzas distinguished himself through his theoretical systemization of the capitalist state in Political Power and Social Classes (1968). First, we highlight the difference between the concepts of the state in Poulantzas and Gramsci and we investigate the other theoretical influences on Cox. Second, we develop a criticism of Cox in relation to his analysis of the internationalization of the state as a function of the supposed global governance.